Calciphylaxis: A Long Road to Cure with a Multidisciplinary and Multimodal Approach - Vasiliki Zoi; Dimitra Bacharaki; Aggeliki Sardeli; Minas Karagiannis; Sophia Lionaki (Case Reports in Nephrology)
Calciphylaxis is a rare yet potentially fatal condition, resulting from ectopic calcification of the small arterioles of the dermis with resulting necrotic lesions infection, sepsis, and death. In hemodialysis patients, its prevalence ranges between 1 and 4%, while mortality amounts to 30–80%. We present in here a 45-year-old female on chronic dialysis with morbid obesity, who was admitted for painful nodules in the lower abdomen and necrotic lesions at the lower extremities. Severe uremia and uncontrolled secondary hyperparathyroidism were the main characteristics in this patient, and thus, a clinical diagnosis of calciphylaxis was made. Treatment modalities included wound care plus antibiotics and analgesics, daily hemodialysis, and strategies targeting calcification with sodium thiosulfate, cinacalcet, and non-calcium-containing binders. A crucial factor for overcoming the infection-lesion vicious circle is thorough and daily care of the lesions. Nursing attention was focused on the motivation of her self-care, for the prevention of institutionalization and the psychological support of the patient and her family. The most intriguing feature was the fact that she experienced several exacerbations during the follow-up time. During the final relapse, she was prescribed hyperbaric oxygen sessions that actually put the disease under control thereafter. The good outcome for this patient was probably related to the combination of close follow-up along with a multidisciplinary approach.